Comparison of three sonographic morphology indices and evaluation of its accuracy in predicting ovarian malignancy - Rai, Snigdha; Shah, Abhishek; Malla, Karishma; Poudel, Sandesh; Upadhyaya, Preetam Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Identifying whether an adnexal mass is benign or malignant is crucial because it guides surgeons regarding the type of operative intervention needed. The aim of this study was to evaluate the accuracy of three sonographic morphology indices (DePriest, Sassone, and Ueland) and the risk of malignancy index for preoperative triaging of adnexal masses and comparing their effectiveness in predicting ovarian malignancy. Methods: A prospective cross-sectional study conducted at Paropakar Maternity and Women’s Hospital from August 2021 to October 2022 underwent an ultrasound scan 48 hours prior to surgery. The specificity, sensitivity, negative predictive value, positive predictive value, and accuracy of all three morphological indices and the risk of malignancy index were calculated and compared. Results: Among 107 patients, 69 (52.3%) had benign tumors, 11 (8.55%) were borderline, and 27 (20.8%) were malignant. The most common malignant ovarian tumor was serous cystadenocarcinoma (14 cases), followed by immature teratoma (5 cases) and granulosa cell tumor (4 cases). The sensitivity of the DePriest, Sassone, and Ueland morphology indices, along with the RMI, was 77.7%, 73%, 85%, and 65%, respectively. Their corresponding specificities were 82.3%, 86.25%, 78.75%, and 73.7%. In terms of accuracy, DePriest achieved 81.48%, Sassone 83%, Ueland 80.37%, and RMI only 74%. Conclusions: Although the Ueland morphology index was the most sensitive in predicting ovarian malignancy, the preoperative diagnostic accuracy was similar across all three morphology indices, while it was notably lower for the risk of malignancy index (RMI).